Preoperative and post‐operative psychosocial interventions for bariatric surgery patients: A systematic review. (22nd January 2020) - David, Lauren A.; Sijercic, Iris; Cassin, Stephanie E.
Summary: Psychosocial interventions are increasingly being utilized to help patients prepare for, and adjust to changes following, bariatric surgery in order to optimize psychosocial adjustment and weight loss. The current systematic review examined the impact of preoperative and post‐operative psychosocial interventions with a behavioural and/or cognitive focus on weight, dietary behaviours, eating pathology, lifestyle behaviours, and psychological functioning. A PsycINFO and Medline search of publications was conducted in March 2019. Two authors assessed retrieved titles and abstracts to determine topic relevance and rated the quality of included studies using a validated checklist. Forty‐four articles (representing 36 studies) met the study inclusion criteria. The current evidence is strongest for the impact of psychosocial interventions, particularly cognitive behavioural therapy, on eating behaviours (eg, binge eating and emotional eating) and psychological functioning (eg, quality of life, depression, and anxiety). The evidence for the impact of psychosocial interventions on weight loss, dietary behaviours (eg, dietary intake), and lifestyle behaviours (eg, physical activity) is relatively weak and mixed. Psychosocial interventions can improve eating pathology and psychosocial functioning among bariatric patients, and the optimal time to initiate treatment appears to be early in the post‐operative period before significant problematic eating behaviours and weight regain occur.